Participation, school and movement expressions (Revista de Investigaciones Universidad del Quindío, 2017)
This article is about the reflections on the underlying civic participation at school, which is marked by traditionalist approaches that ignore the influence and importance of movement expressions developed in the educational field, part of a study called "Crossover" between movement expressions and citizen participation. We developed a case study of teachers in Armenia. The main objective was to understand the relationships on the subject. The methodology was made on the hermeneutic approach, under a multiple case study ethnographic features. In this study, the category descriptions significant movement expressions is expressed. The findings reveal the positions of teachers in traditional models, so it is recommended to put into practice more inclusive actions that allow recognition and scope of training movement expressions that emphasize participation.
Keywords: Movement expressions; citizen participation; traditional models